Children's perceptions of closeness and security in relationships with parents following parental separation - Halpenny, Ann Marie (Trinity College (Dublin, Ireland). School of Psychology, 2005)
Much has been researched and written on the effects of parental separation on children's relationships with their parents. Notably absent from previous research is a focus on close emotional ties and feelings of security in these relationships. An absence of emphasis on the processes which underlie positive or negative experiences of ongoing relationships is also notable. The present study addresses these gaps in the research on parental separation by exploring children's experiences of closeness and security in relationships with parents following parental separation. A primary goal of the present study is to understand and describe how children experience closeness and security in their relationships with parents post-separation. Moreover, the study seeks to explore and identify the configuration of influences which operate to enhance or inhibit closeness and security in relationships with parents in a post-separation family context. Insight into children's perspectives on family transitions is both invaluable and imperative in light of the increasing numbers of separated parents in Ireland and the relatively recent introduction of divorce.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin